Factors influencing the length of hospital stay among patients resident in Blackpool admitted with COPD: a cross-sectional study. Issue 5 (1st September 2012) - Agboado, Gabriel; Peters, Jonathan; Donkin, Lynn
Abstract : Objectives: To identify the differential effects of patient, health service, temporal and geographic factors on length of stay (LOS) for chronic obstructive pulmonary disease (COPD)-related admissions. Design: We used stratified Cox proportional hazard model to evaluate the association between LOS and patient, health service, temporal and geographical factors. Setting: Patients resident in Blackpool, North West England, admitted to the local hospital with COPD. Participants: We used the Admitted Patient Care General Episode Commissioning Dataset for the period 1 April 2005–31 March 2010. We analysed records of admission spells among patients resident in Blackpool aged 40 years or older admitted with a primary diagnosis of COPD. Results: There were 2410 admissions meeting the inclusion criteria over the period. These admissions were attributed to 1172 COPD patients, an average of 2.06 admissions per patient. The median LOS was 6 days (95% CI 6 to 6) while the mean was 9.8 days (95% CI 9.1 to 10.5). Patients were 22% more likely to be discharged earlier in 2009/2010 compared with 2005/2006 (adjusted HR 1.22; p=0.0100). LOS was associated with socioeconomic deprivation with those in the most deprived areas being 35% less likely to be discharged earlier compared with those from the least deprived areas (adjusted HR 0.65; p=0.0010). Conclusions: LOS among COPD patients have reduced over the period of the study. Age, deprivation, Charlson index, specialty of admission and cause of exacerbations were independently associated with LOS. Though there were no significant associations between LOS and season of admission and distance from hospital, there were significant variations in LOS associated with these variables based on selected patient characteristics.